2014
DOI: 10.1108/jaar-11-2013-0090
|View full text |Cite
|
Sign up to set email alerts
|

Board structure and supplementary commentary on the primary financial statements

Abstract: PurposeThis research investigates the relationship between the extent and focus of supplementary narrative commentary (SNC) on amounts reported in the primary financial statements and board structure variables. Design/Methodology/ApproachThe study uses the disclosure index methodology to measure the extent of SNC in annual reports of 167 FTSE 250 companies. Ordinary Least Squares (OLS) regression analysis is employed to examine the association between the extent and focus of SNC and board structure variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…According to Tauringana and Mangena (2014), effective board structures are influenced by the size of the board where larger boards tend to have a greater range of expertise; the proportion of non-executive directors; and the nature of the relevant board committees, particularly the audit committee.…”
Section: Independent Variables Dependent Variable Figure 1: Conceptua...mentioning
confidence: 99%
“…According to Tauringana and Mangena (2014), effective board structures are influenced by the size of the board where larger boards tend to have a greater range of expertise; the proportion of non-executive directors; and the nature of the relevant board committees, particularly the audit committee.…”
Section: Independent Variables Dependent Variable Figure 1: Conceptua...mentioning
confidence: 99%
“…The link between board size and performance has been investigated by several researchers (e.g., Kanak and Boeker, 1994;Van den Berghe and Levrau, 2004;Dalton, 2005, Tauringana andMangena, 2014).The reasoning behind the relationship is that a larger board can bring more experience and knowledge from which the CEO may draw highquality advice (Dalton et al 1999). It has also been suggested that having a larger board can help to provide wider and important linkages for the company (Dalton et al, 1999 Tauringana and Chamisa, 2012).Those who take the contrary view, however, argue that larger boards are less effective in monitoring managers, since they are difficult to co-ordinate and it becomes very difficult to process problems due to the large number of people involved (Kyereboah-Coleman and Biekpe, 2007;Kajola, 2008).…”
Section: Board Sizementioning
confidence: 99%
“…Whereas there are various factors affecting the sustainability commitment of organisations, a growing number of studies have documented that corporate governance is a key driver of SAP (Tauringana & Mangena, 2014;Ong & Djajadikerta, 2020;Haque & Ntim, 2022). These prior studies provide evidence suggesting that corporate governance affects firm's commitment to sustainability.…”
Section: Introductionmentioning
confidence: 99%